A variant form of receptor activator of nuclear factor-κB functions as an osteoprotegerin mimic in bone and cardiac development - Riko Kitazawa; Ryuma Haraguchi; Sohei Kitazawa (Scientific Reports)
Abstract Bone remodeling is tightly regulated by the RANK-RANKL-OPG axis to maintain skeletal integrity. We previously identified a RANK splicing variant, vRANK, which encodes a truncated protein that inhibits osteoclastogenesis and promotes apoptosis. This study examined the regulatory mechanisms of vRANK expression in vitro and its physiological role in vivo using transgenic mice with forced vRANK expression in the monocyte-macrophage lineage and in a systemic manner. In vitro, PMA and TGF-β1 specifically induced vRANK expression, which was completely suppressed by U0126, a MEK1/2 inhibitor, and significantly reduced by Sam68 knockdown, indicating its involvement in RNA splicing regulation. In vivo, RANK-Cre-driven vRANK expression had no skeletal impact, whereas LysM-Cre-driven expression resulted in increased bone mass and suppressed osteoclastogenesis. However, systemic overexpression of vRANK (CAG-CreER) caused perinatal lethality, severe cardiac fibrosis, and immune dysfunction. Notably, myocardial fibrosis in vRANK-overexpressing mice correlated with TGF-β1 upregulation in fibrotic foci, suggesting a pathological feedback loop exacerbating fibrosis. These findings suggest that vRANK functions similarly to OPG in inhibiting osteoclastogenesis while also potentially playing a role in cardiac remodeling and immune regulation.